Euendolithic Cyanobacteria and Proteobacteria Together Contribute to Trigger Bioerosion in Aquatic Environments - Wu, Guimei; Huang, Aiyou; Wen, Yanhong; Wang, Hongxia; Wang, Jiangxin; Luo, Fuguang; Wu, Mingcan (Frontiers in Microbiology, 2022)
Shellfish, mussels, snails, and other aquatic animals, which assimilate limestone (calcium carbonate, CaCO3) to build shells and skeletons, are effective carbon sinks that help mitigate the greenhouse effect. However, bioerosion, the dissolution of calcium carbonate and the release of carbon dioxide, hinders carbon sequestration process. The bioerosion of aquatic environments remains to be elucidated. In this study, the bioerosion of Bellamya spp. shells from the aquatic environment was taken as the research object. In situ microbial community structure analysis of the bioerosion shell from different geographical locations, laboratory-level infected culture, and validated experiments were conducted by coupling traditional observation and 16S rRNA sequencing analysis method. Results showed that bioeroders can implant into the CaCO3 layer of the snail shell, resulting in the formation of many small holes in the shell, which reduced the shell’s density and made the shell fragile. Results also showed that bioeroders were distributed in two major phyla, namely, Cyanobacteria and Proteobacteria. Cluster analysis showed that Cyanobacteria sp. and two unidentified genera (Burkholderiaceae and Raistonia) were the key bioeroders. Moreover, results suggested that the interaction of Cyanobacteria and other bacteria promoted the biological function of “shell bioerosion.” This study identified the causes of “shell bioerosion” in aquatic environments and provided some theoretical basis for preventing and controlling it in the aquatic industry. Results also provided new insights of cyanobacterial bioerosion of shells and microalgae carbon sequestration.